Prevalence and Associated Factors of Chronic Kidney Disease Among Patients Infected With Human Immunodeficiency Virus in Cameroon (Iranian Journal of Kidney Diseases, 2018)
Introduction. Chronic kidney disease (CKD) is frequent amongst human immunodeficiency virus (HIV)-positive patients, and screening is not routinely performed in Sub-Saharan Africa due to resource constraints. We aimed to determine the prevalence of CKD and associated factors in HIV-infected patients in Cameroon. Materials and Methods. A cross-sectional study in Northern Cameroon included HIV-positive patients who attended the HIV clinic. Patients with an estimated glomerular filtration rate less than 60 mL/min/1.73 m² or urinary abnormalities underwent a second measurement 3 months later. Glomerular filtration rate was estimated using the 4-variable Modification of Diet in Renal Disease (MDRD) and the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equations. Logistic regression was used to identify factors associated with CKD. Results. We included 709 participants. The median CD4 count was 219 cells/mL. Proteinuria accounted for 34.4%; leukocyturia, 6.9%; and hematuria, 6.1%. Prevalence of CKD was 44.4% (CKD-EPI) and 47.2% (MDRD). Stages 3 to 5 of CKD were documented in 11.6% using the CKD-EPI and 7.5% using the MDRD. Factors associated with CKD were an age greater than 35 years (odds ratio [OR], 104; 95% confidence interval [CI], 1.02 to 1.06), longer duration of HIV (OR, 2.60; 95% CI, 1.53 to 3.95), history of hepatitis B (OR, 3.04; 95% CI, 1.08 to 8.54), and CD4 cells less than 200 cells/mL (OR, 3.64; 95% CI, 2.55 to 5.21). Conclusions. The prevalence of CKD is high among HIV patients in Cameroon. There is a need of implementing measures to encourage early detection of kidney disease in these patients.